Magnetic Resonance investigation into the mechanisms involved in the development of high-altitude cerebral edema. Issue 1 (January 2017) - Sagoo, Ravjit S; Hutchinson, Charles E; Wright, Alex; Handford, Charles; Parsons, Helen; Sherwood, Victoria; Wayte, Sarah; Nagaraja, Sanjoy; Ng'Andwe, Eddie; Wilson, Mark H; Imray, Christopher HE; ,
Rapid ascent to high altitude commonly results in acute mountain sickness, and on occasion potentially fatal high-altitude cerebral edema. The exact pathophysiological mechanisms behind these syndromes remain to be determined. We report a study in which 12 subjects were exposed to a FiO2 = 0.12 for 22 h and underwent serial magnetic resonance imaging sequences to enable measurement of middle cerebral artery velocity, flow and diameter, and brain parenchymal, cerebrospinal fluid and cerebral venous volumes. Ten subjects completed 22 h and most developed symptoms of acute mountain sickness (mean Lake Louise Score 5.4; p < 0.001 vs. baseline). Cerebral oxygen delivery was maintained by an increase in middle cerebral artery velocity and diameter (first 6 h). There appeared to be venocompression at the level of the small, deep cerebral veins (116 cm 3 at 2 h to 97 cm 3 at 22 h; p < 0.05). Brain white matter volume increased over the 22-h period (574 ml to 587 ml; p < 0.001) and correlated with cumulative Lake Louise scores at 22 h ( p < 0.05). We conclude that cerebral oxygen delivery was maintained by increased arterial inflow and this preceded the development of cerebral edema. Venous outflow restriction appeared to play a contributory role in the formation of cerebral edema, a novel feature that has not been observed previously.